The never-ending feast the anthropology and archaeology of feasting - O'Connor, Kaori (Bloomsbury Academic, 2015)
"Human life is a never-ending feast. Throughout history, and in all parts of the world, feasts have been the primary arena for displays of hierarchy, status and power; a stage upon which loyalties and alliances are negotiated; the occasion for the mobilization and distribution of resources, and the place where identities are created and consolidated through inclusion and exclusion. Feasting in the West in the medieval and modern periods is now well known and central to the study of culture, food and society. But there has been no broad study like this that, while grounded in anthropology and archaeology, also draws upon history and literature for an interdisciplinary look at feasting in the past, outside Europe, without which our knowledge of feasting and understanding of how our global world has been constituted is incomplete. Until now, mainstream feasting studies and food histories have concentrated on European traditions, while others - equally important - have been disregarded and ignored. Focusing on key periods and aspects, looking at feasting in societies not usually dealt with outside highly specialized area studies, combining theory and description, this work examines the never-ending feast in sites that include Mesopotamia, Achaemenid Persia, China, the Mongol Empire and Japan"--